Recent advances in urinary bladder cancer detection. Issue 7 (July 2012) - Bhatt, Jaimin; Cowan, Nigel; Protheroe, Andrew; Crew, Jeremy
Urinary bladder cancer (BCa) is the most common malignancy of the urinary tract. In recent decades, the overall incidence of BCa appears to be on the increase. Despite the increase in incidence, mortality rates in North America and Europe appear to have declined in the last decade, probably due to improved detection and treatment. The mainstay of diagnosis is by cystoscopy, aided with imaging and urine tests (e.g., cytology). This article reviews the recent advances made in detection of primary and recurrent bladder cancer.